Modeling of Moringa oleifera oil solubility in supercritical carbon dioxide - Nguyen, Hoang N. (Animo Repository, 2011)
Moringa oleifera (MO) oil solubility behavior in supercritical carbon dioxide (SC-CO2 ) was investigated at temperature rang e from 35 to 60°C and pressure from 15 to 30MPa. It was observed that pressure played key role on solubility while temperature has minor effect on solubility relative to that of pressure. Solubility was covariant with pressure. Solubility effect with temperature shifted to opposite behavior when pressure has reached the crossover pressure point at 26.38MPa. At p < 26.38MPa, an increased temperature has reduced the solubility. While at p ≥ 26.38MPa, the increased temperature led to an enhanced solubility. Fractionation of the oil during extraction period was observed too. Short chain fatty acids (C14:0, C16:0, C16:1) reduced by 21.87, 7.94 and 9.49% while long chain fatty acids (C20:0, C20:1, C22:0, C24:0) increased by 22.43, 11.42, 21.76 and 35.71% respectively. All C18 fatty acids (stearic, oleic, linoleic, linolenic) were not fractionated significantly during extraction period. However, the effect of the fractionation on the solubility was insignificant. Furthermore, modeling of MO oil solubility in SC-CO 2 was conducted. Del Valle-Aguilera model with root mean square percentage deviation of 6.18% is recommended for high oleic oil solubility in SC-CO2 .